PENGARUH PEMBIAYAAN MURABAHAH DAN MUSYARAKAH MELALUI KREDIT BERMASALAH TERHADAP LIKUIDITAS BANK UMUM SYARIAH - Laksmi Puteri, Sayyida Islamiya; Solekah, Nihayatu Aslamatis (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2018)
One of the causes of bankruptcy is not due to losess incurred but due to the inability to maintain cashflow availability. This study aims to determine the direct relationship of murabahah and musyarakah financing to Islamic bank liquidity through the NPF ratio. This study is descriptive quantitative study using path analysis and purposive sampling to determine the sample. The results of this study indicate that murabahah financing has no effect on NPF but effect the liquidity of Islamic bank. On the contrary, for musyarakah financing affecting NPF but not for liquidity of Islamic bank. It can be implied that due to differences in risk coverage of the two contract (murabahah financing dan musyarakah financing) where murabahah financing the level of risk that may arise will be more borne by the recipient ofÂ  the financing. This contrasts with the musyarakah financing agreement where the risk Non performing loanÂ  can be minimized by sharing the risk in musyarakah financing.However, its relationship with bank liquidity, in fact murabahah financing provides a large contribution considering that islamic bank get certainty about the profit ratio of this financing agreement. As for musyarakah financing, Islamic bank liquidity actually decreases due to uncertainty in the profit sharing ratio it receives. From the result of the intervening test, NPF proxied by the ratio of NPF of Islamic banks did not mediate murabahah financing and musyarakah financing to Islamic bank liquidity.